Data Mining Framework for Network Intrusion Detection using Efficient Techniques - Kaur, Inderjit; Saini, Dr. Pardeep (International Journal of Advanced Engineering, Management and Science, 2023)
The implementation measures the classification accuracy on benchmark datasets after combining SIS and ANNs. In order to put a number on the gains made by using SIS as a strategic tool in data mining, extensive experiments and analyses are carried out. The predicted results of this investigation will have implications for both theoretical and applied settings. Predictive models in a wide variety of disciplines may benefit from the enhanced classification accuracy enabled by SIS inside ANNs. An invaluable resource for scholars and practitioners in the fields of AI and data mining, this study adds to the continuing conversation about how to maximize the efficacy of machine learning methods.